Virtual laboratory for simulation and learning of cardiovascular system function in BME studies - Alher Mauricio Hernández Valdivieso; María Bernarda Salazar Sánchez; David Alexander Urrego Higuita; Ramon Costa-Castelló; Miguel Ángel Mañanas Villanueva (Revista Facultad de Ingeniería Universidad de Antioquia, 2012)
The application of engineering system analysis is a very important field in biomedical engineering (BME) studies: modeling, simulation and control of the most important physiological systems. A virtual laboratory for the analysis and the study of human circulatory system is presented in this paper. This laboratory is based on the compilation of several mathematical models described in the literature. In addition, some model parameters have been tuned by means of experimental data under caffeine stimulus. The computational tool has been built using MATLAB/SIMULINK and EJS, so it combines good computation capabilities with interactivity. The virtual laboratory has been designed in order to understand the operation of the circulatory system under normal conditions, and to predict circulatory variables at different types and levels of stimuli and conditions.